1997
DOI: 10.1021/jp963437v
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigations on Heterogeneous Ziegler−Natta Catalyst Supports:  Stability of the Electron Donors at Different Coordination Sites of MgCl2

Abstract: Ab initio methods were used to study the coordination of electron donors to the (110) and (101) surfaces of a MgCl2 support. The electron donors were alcohols, ketones, esters, and their model compounds. Examination of the interaction energies indicated that the alcohols bind more strongly to the five-coordinated magnesium atom on the (101) surface than to the four-coordinated magnesium atom on the (110) surface. This stability on the (101) surface can be explained in terms of hydrogen bonding between the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…[44,45] In the industrial practice, several procedures are adopted to produced MgCl 2 -based materials, including the mechanical ball-milling of MgCl 2 in the co-presence of TiCl 4 and suitable electron donors, the decomposition of previously synthesized adducts between MgCl 2 and Lewis bases (such as alcohols or ethers) in the presence of TiCl 4 , and the direct chlorination of Mg and Ti alkoxides with AlR n Cl 3-n compounds. [45,[56][57][58][59][60] In the past, Thune and coworkers monitored by FT-IR spectroscopy in ATR mode the direct transformation of the alcoholate precursor into the Ziegler-Natta pre-catalyst in the presence of TiCl 4 and an electron donor. [45,[56][57][58][59][60] In the past, Thune and coworkers monitored by FT-IR spectroscopy in ATR mode the direct transformation of the alcoholate precursor into the Ziegler-Natta pre-catalyst in the presence of TiCl 4 and an electron donor.…”
Section: Introductionmentioning
confidence: 99%
“…[44,45] In the industrial practice, several procedures are adopted to produced MgCl 2 -based materials, including the mechanical ball-milling of MgCl 2 in the co-presence of TiCl 4 and suitable electron donors, the decomposition of previously synthesized adducts between MgCl 2 and Lewis bases (such as alcohols or ethers) in the presence of TiCl 4 , and the direct chlorination of Mg and Ti alkoxides with AlR n Cl 3-n compounds. [45,[56][57][58][59][60] In the past, Thune and coworkers monitored by FT-IR spectroscopy in ATR mode the direct transformation of the alcoholate precursor into the Ziegler-Natta pre-catalyst in the presence of TiCl 4 and an electron donor. [45,[56][57][58][59][60] In the past, Thune and coworkers monitored by FT-IR spectroscopy in ATR mode the direct transformation of the alcoholate precursor into the Ziegler-Natta pre-catalyst in the presence of TiCl 4 and an electron donor.…”
Section: Introductionmentioning
confidence: 99%
“…[4,12] Several experimental and theoretical studies have been dedicated to decipher the role of electron donors on the properties of PP. [4,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Albizatti and Galimberti have discussed the substitutional effects of 1,3 diethers on the isotacticity and productivity of PP. [16] Correa et al based on theoretical work showed that in the absence of donors, the regioregularity of the PP will be less, while in the presence of donors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[151] The amount of electron donors is an adjustable parameter in the polymerization, which is used to control the stereospecificity of the catalyst. [152][153][154][155][156][157][158] Among other effects, the function of the internal donor (diesters) in MgCl 2 -supported catalysts is to stabilize small primary crystallites of MgCl 2 . Another possible function of the internal donor is that, due to the higher acidity of the coordination sites on the (110) face, preferential coordination of the donor on these sites will avoid the formation of Ti species having poor selectivity (yellow sphere in Figure 8), and favor the activity of dimeric sites of the (100) faces (orange sphere in Figure 8), whose environment is chiral, a necessary condition for isospecific polymerization.…”
Section: Heterogeneous Olefin Polymerization Catalystsmentioning
confidence: 99%